Learning to set the reserve price optimally in laboratory first price auctions - Priyodorshi Banerjee; Shashwat Khare; P. Srikant (Games, 2018)
We analyze choices of sellers, each setting a reserve price in a laboratory first price auction with automated equilibrium bidding. Subjects are allowed to gain experience for a fixed period of time prior to making a single payoff-relevant choice. Behavior of more experienced sellers was consistent with benchmark theory: average reserve price for these sellers was independent of the number of bidders and equaled the predicted level. Less experienced sellers however deviated from the theoretical benchmark: on average, they tended to shade reserve price below the predicted level and positively relate it to the number of bidders.
Keywords: C91; D44; 330; reserve price; first-price auction; experience; seller learning